2010
DOI: 10.2353/ajpath.2010.090857
|View full text |Cite
|
Sign up to set email alerts
|

ApoE-Deficient Mice on Cholate-Containing High-Fat Diet Reveal a Pathology Similar to Lung Sarcoidosis

Abstract: Sarcoidosis is a chronic disease of unknown etiology characterized by the formation of non-necrotizing epithelioid granulomas in various organs , especially in the lungs. The lack of an adequate animal model reflecting the pathogenesis of the human disease is one of the major impediments in studying sarcoidosis. In this report , we describe ApoE ؊/؊ mice on a cholatecontaining high-fat diet that exhibit granulomatous lung inflammation similar to human sarcoidosis. Histological analysis revealed well-defined an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 42 publications
1
32
1
Order By: Relevance
“…Unlike human sarcoidosis, the condition in our model is not chronic and improved within 2 weeks, which is consistent with the previous reports, but is a limitation of our study [26,28]. Recently, SAMOKHIN et al [33] reported a model of prolonged pulmonary granulomatosis like human sarcoidosis in ApoE -/-mice. Further study is required to confirm the efficacy of TAK-779 in chronic models with therapeutic protocols.…”
Section: Discussionsupporting
confidence: 79%
“…Unlike human sarcoidosis, the condition in our model is not chronic and improved within 2 weeks, which is consistent with the previous reports, but is a limitation of our study [26,28]. Recently, SAMOKHIN et al [33] reported a model of prolonged pulmonary granulomatosis like human sarcoidosis in ApoE -/-mice. Further study is required to confirm the efficacy of TAK-779 in chronic models with therapeutic protocols.…”
Section: Discussionsupporting
confidence: 79%
“…Dietary cholate has been previously shown to induce inflammation and to potentiate the inflammation induced by a high fat diet. [26][27][28] To avoid this potential confounding variable, we used a diet high in cholesterol and fat, but without cholate supplementation, in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, feeding a WD to Apoe-deficient mice caused an increase in lung cholesterol content and a progression of pathologic changes that included inflammatory cell infiltration at 4 weeks, lipid-laden lung cells and emphysema at 12 weeks, and granuloma formation at 24 weeks (15). Apoe-deficient mice fed a cholate-containing HFD for 16 weeks also developed granulomatous lung inflammation similar to sarcoidosis, as well as progressive pulmonary fibrosis (16). Hypercholesterolemic Apoedeficient mice fed an HFD for 12 weeks developed marked pulmonary fibrotic changes and lung inflammation (17).…”
Section: Apoe and Normal Lung Healthmentioning
confidence: 99%